Colposcopic assessment of the accuracy of cervical cytology screening. Issue 6629 (16th April 1988) - Giles, John A; Hudson, Elizabeth; Crow, Julie; Williams, Denis; Walker, Patrick
Abstract : Two hundred asymptomatic women in a general practice were screened both cytologically and colposcopically for evidence of cervical intraepithelial neoplasia. The prevalence detected by cytology alone was 5%, but the prevalence detected by cytology and colposcopy together was 11%. None of the larger lesions of cervical intraepithelial neoplasia (affecting more than two quadrants of the cervix) was associated with negative cytology. The false negative cytology rate for smaller lesions was 58%. The clinical importance of the smaller lesions that were not accurately detected by cytology screening is unknown. As these lesions affected 6% of the screened population further studies of their clinical course are urgently required. Local destructive treatment in such cases may represent considerable overtreatment. If these lesions prove to be clinically important, however, the results of this study predict an increasing epidemic of preinvasive and invasive disease of the cervix.